2008
DOI: 10.1029/2008gl033377
|View full text |Cite
|
Sign up to set email alerts
|

Cluster multispacecraft determination of AKR angular beaming

Abstract: [1] Simultaneous observations of AKR emission using the four-spacecraft Cluster array were used to make the first direct measurements of the angular beaming patterns of individual bursts. By comparing the spacecraft locations and AKR burst locations, the angular beaming pattern was found to be narrowly confined to a plane containing the magnetic field vector at the source and tangent to a circle of constant latitude. Most rays paths are confined within 15°of this tangent plane, consistent with numerical simula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
101
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(115 citation statements)
references
References 25 publications
14
101
0
Order By: Relevance
“…Cairns et al [27] have demonstrated how the radiation, generated just below the electron cyclotron frequency, may successfully couple onto the upper branch of the plasma dispersion relation and escape. This model assumes near field-aligned R mode polarization prior to escape, as observed by the Cluster satellite mission [28]. However, it is well known that the radiation is generated near perpendicular to the magnetic field in the X mode [17] and will undergo strong resonant absorption when the radiation encounters the second harmonic layer [26].…”
mentioning
confidence: 99%
“…Cairns et al [27] have demonstrated how the radiation, generated just below the electron cyclotron frequency, may successfully couple onto the upper branch of the plasma dispersion relation and escape. This model assumes near field-aligned R mode polarization prior to escape, as observed by the Cluster satellite mission [28]. However, it is well known that the radiation is generated near perpendicular to the magnetic field in the X mode [17] and will undergo strong resonant absorption when the radiation encounters the second harmonic layer [26].…”
mentioning
confidence: 99%
“…9, allows for simultaneous observation of the same AKR burst from slightly different vantage points. This has enabled both an accurate determination of the source location and led to a comprehensive characterization of the AKR beaming pattern (Mutel et al 2003(Mutel et al , 2004(Mutel et al , 2008.…”
Section: Betatron and Stochastic Accelerationmentioning
confidence: 99%
“…Because the Cluster constellation provides six independent baselines for calculating propagation time differences according to (2.1), the AKR source location (with only three unknowns) is over-determined and can be localized to within a volume by minimizing the signed sum to within the timing measurement uncertainties (Mutel et al 2003(Mutel et al , 2004. Using this technique Mutel et al (2004Mutel et al ( , 2008 determined the intrinsic properties of AKR sources and beaming characteristics. They found that AKR is generally emitted from individual sources located in the nightside auroral zone (see Fig.…”
Section: Betatron and Stochastic Accelerationmentioning
confidence: 99%
See 1 more Smart Citation
“…The AKR angular beaming follows such laminar source model. After being emitted and passing through high-density regions, the radiation is refracted upwards (Mutel, Christopher & Pickett 2008;Menietti et al 2011). …”
Section: Introductionmentioning
confidence: 99%